Cycling and running performance, not anthropometric factors, are associated with race performance in a triple Iron Triathlon - Knechtle, B.; Duff, B.; Amtmann, G.; Kohler, G. (Research in Sports Medicine, 2007)
Sixteen well-trained and well-experienced male Caucasian triathletes participated in World Championship Triple Iron Triathlon 2006 in Moosburg, Kärnten, Austria, which required athletes to perform 11.6 km swimming, 540 km cycling, and 126.6 km running within a time limit of 58 hours. Body mass, body height, skinfold thicknesses, circumferences of extremities, skeletal muscle mass, and body fat were measured. The results showed that race time was not significantly influenced by the anthropometric properties (p > 0.05). No significant influence was observed between race time and the calculated parameters of body mass index (BMI), body fat, and skeletal muscle mass (p > 0.05). In contrast, cycling performance (r2 = 0.49, p < 0.01) and running performance (r2 = 0.73, p < 0.01) are associated with total race performance. It summery, in an ultratriathlon, BMI, body height, skinfold thicknesses, circumference of extremities, skeletal muscle mass, and body fat have no influence on race performance in world-class ultratriathletes. Total race performance is associated with performance in cycling and running, not in swimming.